Calcium Phosphate Incorporated Bacterial Cellulose-Polyvinylpyrrolidone Based Hydrogel Scaffold: Structural Property and Cell Viability Study for Bone Regeneration Application - Basu, Probal; Saha, Nabanita; Alexandrova, Radostina; Saha, Petr (Polymers, 2019)
This work focuses on the analysis of structural and functional properties of calcium phosphate (CaP) incorporated bacterial cellulose (BC)-polyvinylpyrrolidone (PVP) based hydrogel scaffolds referred to as "CaP/BC-PVP". CaP is incorporated in the scaffolds in the form of hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP) in different concentrations (β-TCP: HA (w/w) = 20:80, 40:60, and 50:50). The scaffolds were characterized on the basis of porosity, thermal, biodegradation, mechanical, and cell viability/cytocompatibility properties. The structural properties of all the hydrogel scaffolds show significant porosity. The biodegradation of "CaP/BC-PVP" scaffold was evaluated following hydrolytic degradation. Weight loss profile, pH change, scanning electron microscopy (SEM), and Fourier Transform Infrared Spectroscopy (FTIR) study confirm the significant degradability of the scaffolds. It is observed that a 50:50_CaP/BC-PVP scaffold has the highest degree of degradation. On the other hand, the compressive strengths of CaP/BC-PVP hydrogel scaffolds are found between 0.21 to 0.31 MPa, which is comparable with the human trabecular bone. The cell viability study is performed with a human osteosarcoma Saos-2 cell line, where significant cell viability is observed in all the hydrogel scaffolds. This indicated their ability to facilitate cell growth and cell proliferation. Considering all these substantial properties, CaP/BC-PVP hydrogel scaffolds can be suggested for detailed investigation in the context of bone regeneration application.
Keywords: calcium phosphate; bone regeneration; degradation; mechanical property; bacterial cellulose; hydrogel scaffolds